A Scientometric Review of Agroecology and its Role in Sustainable Food Systems - Judijanto, Loso (West Science Nature and Technology, 2025)
This study presents a scientometric review of the global research landscape on agroecology and its role in sustainable food systems, using data retrieved from the Scopus database and analyzed through VOSviewer. By examining co-authorship patterns, institutional collaborations, keyword co-occurrence, and thematic evolution, the study identifies key contributors, dominant research themes, and emerging trends within the field. Central concepts such as agroecology, sustainability, climate change, and food security form the core of scholarly discourse, reflecting the multidimensional nature of agroecology as both a scientific approach and a socio-political movement. The analysis highlights a growing shift in research focus—from traditional agronomic practices toward systemic issues like food sovereignty, adaptation, and justice-based food system transformation. This review contributes to a deeper understanding of how agroecology has evolved and provides strategic insights for researchers, policymakers, and practitioners engaged in advancing equitable and resilient food systems globally.